Effect of Critical Thinking, Learning Independence, and Gotong Royong in P5 Merdeka Curriculum - Yusniar Yusniar; Elpisah Elpisah; Syarifuddin Syarifuddin (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2025)
This study aims to analyze the effect of critical thinking ability, learning independence, and mutual cooperation attitude in the P5 dimension of the Merdeka Curriculum on the learning achievement of IPAS class V UPT SPF SDN Inpres Perumnas I Makassar students, both partially and simultaneously. This study used a quantitative approach with a total sampling method, involving the entire population of 40 students from two classes. Data were collected through questionnaires and analyzed using multiple regression, t-test, and F-test with the help of SPSS 26. The results showed that partially, critical thinking ability (X1), student learning independence (X2), and mutual cooperation attitude (X3) had a positive and significant influence on IPAS learning achievement (Y). Simultaneously, the three variables also jointly influence student learning achievement.This finding confirms that the P5 dimension in the Merdeka Curriculum, especially in the aspects of critical thinking, learning independence, and mutual cooperation, plays an important role in improving students' IPAS learning achievement. Therefore, implementing learning strategies that encourage these three aspects can be an effective step in improving the quality of education in elementary schools